THE EFFECT OF PINEAPPLE (ANANAS COMOSUS L. MERR) LEAF FIBER’S VOLUME FRACTION TOWARD FLEXURAL STRENGTH OF FLOWABLE RESIN COMPOSITE - Shilfina Rufaida; Eko Hadianto; Muhamat Muhtar Abdurrohman (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Composite resin is one of dental restorative materials that have a high aesthetic value. Fiber Reinforced Composite (FRC) is a combination material between polymer matrix and fiber and it is used as an alternative material to improve mechanical properties. The mechanical strength can be affected by the fraction of fiber volume used. This study aims is to know the effect of fraction of pineapple leaf fiber volume to the strength of composite resin flexural with pineapple leaf fiber concentration 0%, 1%, and 1,5%.Method: This study is a true experimental one with only control group design post-test. The total sample used was 27 specimens with a size 25x2x2 mm. The sample was divided into 3 groups, resin composite with a fraction of pineapple leaf fiber pineapple volume 0%, 1%, 1,5%. Flexural strength was tested by a three-point bending test in the universal testing machine.Result: The result of flexural strength in flowable resin composite with fraction of pineapple leaf fiber volume 0% (99,48 MPa ± 4,38), fraction volume 1% (131,40 MPa ± 5,39) and fraction volume 1,5% (148,88 MPa ± 3,74). One way ANOVA test showed that there was a significant difference in every group. Post Hoc test showed that there was a significant difference among groups. Conclusion: The fraction of pineapple leaf fiber (Ananas Comosus L. Merr) volume affects to the flexural strength of flowable resin composite. Flowable resin composite fraction of pineapple leaf fiber volume 1,5% has the highest flexural strength.